2022
DOI: 10.2459/jcm.0000000000001380
|View full text |Cite
|
Sign up to set email alerts
|

Immediate coronary angiography in patients with out-of-hospital cardiac arrest without ST-segment elevation: a meta-analysis of randomized trials

Abstract: Current guidelines recommend immediate coronary angiography in patients with out-of-hospital cardiac arrest (OHCA) who have a high probability of acute coronary syndrome (ACS), demonstrated by ST-segment elevation (STE) on electrocardiogram after the return of spontaneous circulation (ROSC) is achieved. 1 Otherwise, the benefit of the procedure has been debatable for OHCA patients without STE on electrocardiogram. Since there is no meta-analysis comprising only randomized controlled trials (RCTs), we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The reported results are consistent with other recently published clinical trials and meta-analyses 2–4 . Perhaps most interestingly, the authors reported a significant improvement in 30-day or in-hospital (short-term) neurological outcomes with no heterogeneity 1 . These results are interesting because a concurrent meta-analysis has shown a significant benefit of ECPR in patients with OHCA, but only in the long term (≥90 days after cardiac arrest) 2…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The reported results are consistent with other recently published clinical trials and meta-analyses 2–4 . Perhaps most interestingly, the authors reported a significant improvement in 30-day or in-hospital (short-term) neurological outcomes with no heterogeneity 1 . These results are interesting because a concurrent meta-analysis has shown a significant benefit of ECPR in patients with OHCA, but only in the long term (≥90 days after cardiac arrest) 2…”
supporting
confidence: 89%
“…[2][3][4] Perhaps most interestingly, the authors reported a significant improvement in 30-day or in-hospital (short-term) neurological outcomes with no heterogeneity. 1 These results are interesting because a concurrent meta-analysis has shown a significant benefit of ECPR in patients with OHCA, but only in the long term (!90 days after cardiac arrest). 2 As has been pointed out, the observed differences in results reflect the substantial heterogeneity in confounders because of patient selection, cost-effectiveness, and local technical and logistical challenges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the timing of the early coronary angiography was quite similar between the two trials (2.3 h in the COACT trial versus 2.9 h in the Tomahawk study), while in the delayed-angiography subgroups it was 121.9 h and 46.9 h in the COACT trial and the Tomahawk trial respectively. Recent meta-analyses, including only RCTs in NSTE ACS patients indicate no benefit of early CAG over delayed CAG with respect to both 30-day all-cause mortality and residual neurological status 13,14 …”
mentioning
confidence: 99%
“…Recent meta-analyses, including only RCTs in NSTE ACS patients indicate no benefit of early CAG over delayed CAG with respect to both 30-day allcause mortality and residual neurological status. 13,14 In the current issue of the Journal the paper by Lazzeri et al 18 provides the experience of a single hub center for refractory cardiac arrest, where the vast majority of the local OHCA patient candidates for extracorporeal membrane oxygenation are referred. In their retrospective, observational study the authors try to assess whether a coronary angiography within 6 h from hospital admittance (followed by PCI when needed) is associated with a mortality benefit in all patients with an acute coronary syndrome, including patients with non-ST-segment elevation myocardial infarction.…”
mentioning
confidence: 99%